Main Sources of Unification of the Civil and Commercial Law in the EU - E. A. Horrmann (Московский журнал международного права, 2013)
This article is dedicated to the theoretical and practical aspects of the unification and harmonization of the civil and commercial law in the EU. The article provides the information about main sources of the European law, eg. Treaty on European Union (Consolidated version 2012) and Treaty on the Functioning of the European Union (Consolidated version 2012). The author also thoroughly analyses and estimates the Rome I and Rome II regulations, as the most important and successful acts concerning unification and harmonisation of the European civil and commercial law nowadays.